Apoplastic Expression of Yeast-Derived Invertase in Potato : Effects on Photosynthesis, Leaf Solute Composition, Water Relations, and Tuber Composition - Heineke, Dieter (1992)
In potato plants (Solanum tuberosum), a chimeric yeast-derived invertase gene fused to a 35S cauliflower mosaic virus promoter has been expressed. The protein was targeted to the cell wall by using the signal peptide of proteinase inhibitor II fused to the amino terminus of the yeast invertase. The transformed plants had crinkled leaves, showed a reduced growth rate, and produced fewer tubers. Although in the apoplast of the leaves of the transformed plants the content of glucose and fructose rose by a factor of 20, and that of sucrose declined 20-fold, 98% of the carbohydrate in the phloem sap consisted of sucrose, demonstrating the strong specificity of phloem loading. In the leaf cells of the transformed plants, glucose, fructose, and amino acids, especially proline, were accumulated. Consequently, the osmolality of the cell sap rose from 250 to 350 mosmol/kg. Our results show that the observed 75% decrease of photosynthesis is not caused by a feedback regulation of sucrose synthesis and is accompanied by an increase in the osmotic pressure in the leaf cells. In the transformed plants, not only the amino acid to sucrose ratio in the phloem sap, but also the amino acid and protein contents in the tubers were found to be elevated. In the tubers of the transformed plants, the protein to starch ratio increased.